Optimization Formula and SPF Test of Lotion from Essential Oil of Patchouli Leaves (Pogostemon cablin Benth.) - Anjaly Rizkya Fazariana; Fathnur Sani K; Indri Maharini (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
An increase in the ultraviolet (UV) index poses severe health risks by inducing harmful effects on the skin, such as sunburn, erythema, skin darkening, premature ageing, and skin cancer. These risks are mitigated through sunscreens with high Sun Protection Factor (SPF) values (15). Natural sources of high SPF include patchouli leaf essential oil, which contains flavonoids. Flavonoid compounds with double bonds can absorb UV-A and UV-B rays, protecting against their harmful effects. The purpose of this study was to find the best formula and observe its impact on the physical characteristics of the preparation and SPF activity. Formula optimization used Design Expert software 13 with the simplex lattice design method. The optimized variables were TEA and stearic acid as emulsifying agents. The results of the optimum formula composition consisted of 4% TEA and 5% stearic acid. The optimum skin protection lotion preparation has a yellow color, a distinctive smell of patchouli oil, a semi-solid shape and a thick texture. The pH parameters of 7.7±0.09, adhesion of 2.34±0.06 seconds, spreadability of 6.85±0.02 cm and viscosity of 4503.3±219.39 Cp. Patchouli leaf essential oil and lotion have ultra-category SPF values with oil SPF value of 27.86±1.07 and lotion preparation of 27.65±1.75 preparation is also homogeneous with pH parameters of 7.7±0.09, adhesion of 2.34±0.06 seconds, spreadability of 6.85±0.02 cm and viscosity of 4503.3±219.39 Cp. Patchouli leaf essential oil and lotion have ultra-category SPF values with oil SPF value of 27.86±1.07 and lotion preparation of 27.65±1.75.